Grassroots INGOs in Africa: Perspectives on What They Are (and Are Not?). (February 2022) - Appe, Susan
This research explores philanthropic transfers and exchanges between and among the North and the South, namely, through grassroots international nongovernmental organizations (INGOs), which tend to fall outside of the aid industry. The broad research question that frames this study is as follows: How do these organizations, grassroots INGOs in the global North and their partner organizations in the global South, represent and legitimize their work within the larger realm of development aid in Africa? The research conducts a comparative case study through the analysis of the narratives via organizational stories and artifacts produced and used by grassroots INGOs in the United States and partner organizations in Kenya. The findings show how grassroots INGOs distinguish themselves from what are the traditional images of global philanthropic exchanges and development aid, producing disassociative claims. The research derives a set of properties of grassroots INGOs to explain these perceived distinctions.